Stress-concentration reduction and mechanical performance improvement of Cf/SiC composite-to-superalloy joints by using topology optimization - Xu Chen; Qiang Yang; Linfeng Qu; Yingxin Wang; Fu Wang; Dichen Li (Materials & Design, 2022)
High-stress concentrations form in Cf/SiC composite-to-superalloy joints because of their large modulus mismatch. It deteriorates the mechanical performance of the joined parts and even causes failure. This paper proposes a global stress constrained bimaterial topology optimization method with an adjustable compliance objective to design the joint structure to alleviate the stress concentration in Cf/SiC composite-to-superalloy joints and improve their mechanical properties. Using a numerical FEA modeling simulation and experimental method, the effectiveness of the optimized joining structure was validated. The stress concentration in the joints under three-point-bending test was significantly reduced in comparison to that of the traditional flat and zigzag joints, and the flexural strength was greatly improved by 120% to 143% compared with that of the zigzag joint. The present study provides a new consideration to enhance the mechanical properties of Cf/SiC composite-to-superalloy joints from a structural point of view and compensates for the traditional improvement method of only optimizing interlayer materials.